Bibliometric Foundations: Tracking the Footprint of Green Finance and Financial Institutions in Global Research - Astiwardhani, Winny (Profesional Muda Cendekia Publishing, 2023)
This study evaluates research trends in the context of green finance relating to financial institutions, particularly banks, using bibliometric analysis of Scopus data between 2012 and 2023. Green finance, as a key focus, has evolved along with the increasing awareness of environmental issues and climate change. Chinese contributions dominate in this study, showing a strong interest and commitment to green finance. This bibliometric analysis presents a network of related keywords, highlighting terms such as green finance, sustainable development, China, renewable energy, and others. Increased research interest in green finance has been seen since 2020, reflecting the growing attention to green finance, especially in China. From the citation analysis, there are highly cited papers that cover important issues, including the role of banks in green finance innovation, its impact on environmental change, and the implementation of greener financial practices. Cluster analysis shows three main groups: green finance concepts and principles, implementation of green finance practices, and long-term implications of green finance on the environment. These clusters illustrate the conceptual foundations, implementation practices, and long-term impacts of green finance in the context of banking and financial institutions.